Breast and Cervical Cancer Screening Literacy Among Korean American Women: A Community Health Worker–Led Intervention - Han, Hae-Ra (Am J Public Health, 2017)
Objectives. To test a community health worker (CHW)-led health literacy intervention on mammogram and Papanicolaou test screening among Korean American women. Methods. We conducted a cluster-randomized trial at 23 ethnic churches in the Baltimore, Maryland–Washington, DC, metropolitan area between 2010 and 2014. Trained CHWs enrolled 560 women. The intervention group received an individually tailored cancer-screening brochure followed by CHW-led health literacy training and monthly telephone counseling with navigation assistance. Study outcomes included receipt of an age-appropriate cancer screening test, health literacy, cancer knowledge, and perceptions about cancer screening at 6 months. Results. The odds of having received a mammogram were 18.5 (95% confidence interval [CI] = 9.2, 37.4) times higher in the intervention than in the control group, adjusting for covariates. The odds of receiving a Papanicolaou test were 13.3 (95% CI = 7.9, 22.3) times higher; the odds of receiving both tests were 17.4 (95% CI = 7.5, 40.3) times higher. Intervention effects also included increases in health literacy and positive perceptions about cancer screening. Conclusions. A health literacy–focused CHW intervention successfully promoted cancer-screening behaviors and related cognitive and attitudinal outcomes in Korean American women.